Multimetallic Hierarchical Aerogels: Shape Engineering of the Building Blocks for Efficient Electrocatalysis - Cai, Bin; Dianat, Arezoo; Huebner, Rene; Liu, Wei; Wen, Dan; Benad, Albrecht; Sonntag, Luisa; Gemming, Thomas; Cuniberti, Gianaurelio (Giovanni); Eychmueller, Alexander (Advanced Materials, 2017)
Researchers demonstrate a new class of hierarchical aerogels composed of multimetallic Ni-PdXPtY nano-building blocks (NBBs) with continuously engineered shape and compositions. Several important features can be highlighted, such as the morphology of the NBBs has been in situ engineered from hollow nanospheres to dendritic nanocrystals, which have been applied to construct aerogel monoliths by a facile and large-scalable sol–gel method. This results in aerogels with hierarchical structures organizing the nanoscale-regulated architecture and macroscale 3D network structure, leading to an abundance of exposed edges and a high surface area
CRIS-Team Scopus Importer:2022-04-14
Keywords: aerogels; electrocatalysts; ethanol oxidation; hierarchical structures; sol–gel processes